Role of operating parameters in improving stability of once through steam generator used in SFR. (May 2021) - Pathak, S.P.; Velusamy, K.
Highlights: We develop a thermal hydraulic model for sodium heated steam generators. We validate model by conducting experiments on a 5.5 MW capacity steam generator. Flow instability is observed in the steam generator at 20% load condition. Various options to improve steam generator stability are investigated. We establish that stable regime can be widened by reducing sodium flow-rate. Abstract: Once through type steam generators used in Sodium cooled Fast Reactors (SFR) are prone to flow instability. Operating parameters of the steam generators play vital role in defining a stable operating regime. Towards understanding this, a thermal hydraulic model is developed. The developed model is validated by performing experiments on a 19-tube model of straight vertical steam generator of 5.5 MW capacity. Flow instability is observed at 20% load conditions and the correlation developed by France et al. (1986) for predicting dynamic stability is validated. Various options for improving the stability, including increasing single-phase water flow resistance are investigated. It is found that by tweaking the operating parameters, viz., reducing sodium flow rate or increasing steam-side pressure, the stable operating regime can be widened, without increasing the water-side orifice pressure drop. This study is directed towards finalizing low power operating strategy of future Indian experimental fast reactor, FBTR-2.